Functional epitopes and neutralizing antibodies of vaccinia virus - Peng, Fenghao; Hu, Naijing; Liu, Yingjun; Xing, Cong; Luo, Longlong; Li, Xinying; Wang, Jing; Chen, Guojiang; Xiao, He; Liu, Chenghua; Shen, Beifen; Feng, Jiannan; et al. (Frontiers in Microbiology, 2023)
Smallpox is an infectious disease caused by the variola virus, and it has a high mortality rate.Historically it has broken out in many countries and it was a great threat to human health. Smallpox was declared eradicated in 1980, and Many countries stopped nation-wide smallpox vaccinations at that time. In recent years the potential threat of bioterrorism using smallpox has led to resumed research on the treatment and prevention of smallpox. Effective ways of preventing and treating smallpox infection have been reported, including vaccination, chemical drugs, neutralizing antibodies, and clinical symptomatic therapies. Antibody treatments include anti-sera, murine monoclonal antibodies, and engineered humanized or human antibodies. Engineered antibodies are homologous, safe, and effective. The development of humanized and genetically engineered antibodies against variola virus via molecular biology and bioinformatics is therefore a potentially fruitful prospect with respect to field application. Natural smallpox virus is inaccessible, therefore most research about prevention and/or treatment of smallpox were done using vaccinia virus, which is much safer and highly homologous to smallpox. Herein we summarize vaccinia virus epitope information reported to date, and discuss neutralizing antibodies with potential value for field application.